2016
DOI: 10.3109/13668250.2016.1178220
|View full text |Cite
|
Sign up to set email alerts
|

In plain sight but still invisible: A structured case analysis of people with mild intellectual disability or borderline intellectual functioning

Abstract: Background There has been substantial increase in the number of people with mild intellectual disability (MID) or borderline intellectual functioning referred to long-term care. Insight into the specific characteristics and needs of these people is essential to provide appropriate support and gain insight into the increase in referrals. Method This retrospective descriptive study was based on a structured case analysis of a sample of 250 participants.Results Mental health problems and exposure to social and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…They have been found to experience lower levels of psychological well‐being, poorer physical health, reduced access to social capital, more problems in personal and social relationships, a lower employment rate, and a lower income than their peers (e.g., Ferrari, ; Peltopuro et al, ; Seltzer et al, ; Stancliffe & Lakin, ; Tymchuk, Lakin, & Luckasson, ; Vaillant & Davis, ). Moreover, several studies showed that the prevalence of mental health problems is relatively high among people with MID and BIF (Cooper, Smiley, Morrison, Williamson, & Allan, ; Dusseljee, Rijken, Cardol, Curfs, & Groenewegen, ; Emerson, Einfeld, & Stancliffe, ; Nouwens, Lucas, Embregts, & van Nieuwenhuizen, ).…”
Section: Introductionmentioning
confidence: 99%
“…They have been found to experience lower levels of psychological well‐being, poorer physical health, reduced access to social capital, more problems in personal and social relationships, a lower employment rate, and a lower income than their peers (e.g., Ferrari, ; Peltopuro et al, ; Seltzer et al, ; Stancliffe & Lakin, ; Tymchuk, Lakin, & Luckasson, ; Vaillant & Davis, ). Moreover, several studies showed that the prevalence of mental health problems is relatively high among people with MID and BIF (Cooper, Smiley, Morrison, Williamson, & Allan, ; Dusseljee, Rijken, Cardol, Curfs, & Groenewegen, ; Emerson, Einfeld, & Stancliffe, ; Nouwens, Lucas, Embregts, & van Nieuwenhuizen, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they may experience limitations in their social life [1], have fewer friends, and restrictive access to social and leisure activities compared to typically developed individuals [2]. Moreover, many persons with MID or BIF are exposed to a range of negative family conditions, such as divorce, inconsistent parenting, parents with mental health problems, and/or a low financial status [3]. Also, due to the relationship between adverse child, family/contextual factors and mental health problems [4,5], many persons with MID or BIF suffer from mental health problems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, important differences have been demonstrated between persons with MID and BIF. For example, Nouwens, Lucas, Embregts, and Van Nieuwenhuizen [3] have shown that persons with BIF encounter more negative individual and social risk factors than persons with MID. Additionally, Emerson, Einfeld, and Stancliffe [11] stated that BIF is associated with poorer mental health in later childhood and adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the diversity within the population of persons with MID or BIF suggests possible heterogeneity and, consequently, the need for a differentiated approach. Better insight and understanding of this heterogeneity can help in attempts to develop more individualized support programs meeting the support needs of persons with MID or BIF [19]. …”
Section: Introductionmentioning
confidence: 99%